TEACHER PERFORMANCE ON STUDENT LEARNING MOTIVATION IN EFFORTS TO IMPROVE THE QUALITY OF EDUCATION at MTs DARUL HIKMAH, SUMEDANG - Arifin; Sinaga, Obsatar, Paroli; Listiana, Teti (CENTRAL ASIA AND THE CAUCASUS, 2022)
Learning has an important role in improving the quality of education through the application of national education standards. This study aims to analyze the analysis of teacher performance on student learning motivation in an effort to improve the quality of education at Mts Darul Hikmah Sumedang. The method used in this study is a quantitative research method. Data collection techniques using questionnaires, and data analysis techniques using validity tests, reliability tests, classical assumption tests, regression tests, linearity tests and path analysis. The results of the analysis of the effect of teacher performance on students' learning motivation and its implications for the quality of education at MTs Darul Hikmah Sumedan, that the framework of the relationship between the variable path of teacher performance on the quality of education and the variable of student motivation on the quality of education obtained the equation Z = PZXx + PZYY+PZ ε2 or Z = 0.502X + 0.495 Y + 0.1414 2. The Path Coefficient of Teacher Performance on Education Quality (pXZ) is 0.502, and the Path Coefficient of Student Learning Motivation on Education Quality (pYZ) is 0.495. Suggestions from this study are to improve the quality of education through teacher performance and student learning motivation so that the competence of teachers is further improved, especially the problem of learning methods and mastery of information technology.